Clinico-epidemiological study of dermatophytosis in teaching hospital of North Karnataka - Guruprasad, K. Y.; Javed, Mohammed Waseem; Roopa, C.; Ansari, Humera; Takalkar, A. A. (International Journal of Research in Dermatology, 2019)
Background: Although fungi are worldwide, only few of them are considered pathogenic. The pathogenic fungi may give rise to infections in animals and human beings. Skin infection due to dermatophytes has become a significant health problem of late equally affecting children, adolescents and adults. Depending on the climate and culture, the clinical picture can vary enormously. The objective of the study was to study the clinical and diagnostic spectrum of dermatophytosis at Dermatology OPD of KBNIMS, Kalaburagi. Methods: The present descriptive study was conducted in Dermatology OPD in teaching Hospital of North Karnataka. Results: Majority of the subjects were from 21 to 40 years age group i.e. 44.58% followed by 36.4% from 0 to 20 years age group. Out of 250 patients, majority were males i.e. 70.4% whereas 29.6% were females. More than half i.e. 174 (69.6%) out of 250 patients were KOH positive. Prevalence of culture positive specimen was found to be 40%. T. cruris (35%) and corporis (32%) were most common infections in our study. 31% of cases T. mentagrophyte was observed as most common isolate on culture.. Conclusions: In our study, most common dermatophytic infection was T. cruris (35%). Only 40% were culture positive and among which Trichophton mentagrophyte was commonly seen isolate. Low socioeconomic status, overcrowding and compromised personal hygiene with tropical climate are prevalent factors in our study.